Gold-TiO2@gallic acid nanospheres for enhanced surface-assisted laser desorption/ionization mass spectrometry imaging. (March 2022) - Sun, Ruiyang; Tang, Weiwei; Li, Bin
Highlights: An efficient SALDI substrate, Au-TiO2 @GA nanospheres coated ITO glass slide, has been prepared for SALDI MSI. This SALDI substrate provides higher detection sensitivity, lower background interference, dual-polarity detection, and enhanced ionization efficiency of neutral lipids. The spatial distributions of various endogenous components in the mouse tissues, G. elata, and potato tubers were visualized by tissue deposition on SALDI substrate. Abstract: Surface-assisted laser desorption/ionization (SALDI) mass spectrometry imaging (MSI) can effectively reduce the matrix interference and ion suppression that occurred in traditional matrix-assisted laser desorption/ionization (MALDI) MSI. In this work, gold nanoparticles (AuNPs) modified TiO2 nanospheres were synthesized and modified with gallic acid (GA) to fabricate Au-TiO2 @GA nanospheres (Au-TiO2 @GA NSs). The SALDI substrate was prepared by coating the ITO glass slide with Au-TiO2 @GA NSs using a gas-assisted electric sprayer. Compared with often-used MALDI matrices such as 2, 5-dihydroxybenzoic acid (DHB), 2-mercaptobenzothiazole (MBT), 1, 5-diaminonaphthalene (DAN), 2, 5-dihydroxyacetophenone (DHA), and 9-aminoacridine (9-AA), the Au-TiO2 @GA NSs provide higher detection sensitivity, lower background interference, dual-polarity detection and enhanced ionization efficiency of various endogenous molecules, particularly to the detection of neutral lipids. SALDI MSI could be straightforwardly performed on biological tissues thaw-mounted on the prepared substrate. The spatial distribution of various molecular species was unraveled in the mouse brain, kidney, and liver tissues. Not limited to animal tissues, Au-TiO2 @GA NSs showed a more universal application to SALDI MSI of secondary metabolites in plant tissues. The spatial distribution of various natural products was mapped using SALDI MSI, such as parishins in Gastrodia elata tuber (Tianma) and glycoalkaloids in potato tuber. This work provides a high-efficient and high-compatible nanomaterial for SALDI MSI Graph abstract: Image, graphical abstract